2016
DOI: 10.1007/978-3-319-22536-4_9
|View full text |Cite
|
Sign up to set email alerts
|

Droplets, Bubbles and Ultrasound Interactions

Abstract: The interaction of droplets and bubbles with ultrasound has been studied extensively in the last 25 years. Microbubbles are broadly used in diagnostic and therapeutic medical applications, for instance, as ultrasound contrast agents. They have a similar size as red blood cells, and thus are able to circulate within blood vessels. Perfluorocarbon liquid droplets can be a potential new generation of microbubble agents as ultrasound can trigger their conversion into gas bubbles. Prior to activation, they are at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 39 publications
1
34
0
Order By: Relevance
“…Indeed, recent reports have demonstrated that application of laser-generated focused ultrasound to microgels can enhance drug release kinetics 8,9 . While the effect of ultrasound of microgel deformability has not been studied previously, interactions between ultrasound and highly deformable droplets and microbubbles have been studied in the last few decades for diagnostic and therapeutic applications 10 . Ultrasound contrast agent (UCA) microbubbles are used in combination with ultrasound insonification for numerous applications, including contrast-enhanced ultrasound imaging 11,12 , enhancing effectiveness of High Intensity Focused Ultrasound (HIFU) treatments 13 , multiple scattering based quantitative ultrasound tissue characterization 14 , targeted drug delivery 15 , enhancing drug uptake by tumors 16 , and non-invasive molecular imaging 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, recent reports have demonstrated that application of laser-generated focused ultrasound to microgels can enhance drug release kinetics 8,9 . While the effect of ultrasound of microgel deformability has not been studied previously, interactions between ultrasound and highly deformable droplets and microbubbles have been studied in the last few decades for diagnostic and therapeutic applications 10 . Ultrasound contrast agent (UCA) microbubbles are used in combination with ultrasound insonification for numerous applications, including contrast-enhanced ultrasound imaging 11,12 , enhancing effectiveness of High Intensity Focused Ultrasound (HIFU) treatments 13 , multiple scattering based quantitative ultrasound tissue characterization 14 , targeted drug delivery 15 , enhancing drug uptake by tumors 16 , and non-invasive molecular imaging 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Additional antivascular approaches include photodynamic therapy (PDT)18192021, embolotherapy22232425, antivascular ultrasound therapy (AVUT)262728, and photothermolysis29. These approaches have been developed to shut down or destroy existing blood vessels.…”
mentioning
confidence: 99%
“…Moreover droplets are more stable than gas bubbles in blood circulation at 37°C because droplets maintain their liquid core in the circulation avoiding gas dissolution (Lanza and Wickline, 2001;Lea-Banks et al, 2019). Stable PFC emulsions, commonly used droplets, can be prepared to~200 nm in diameter (Fabiilli et al, 2010), which is beneficial for circulating for a longer time in vivo, passing into tissues or cells, and enhancing the EPR effect (Shpak et al, 2016). More interestingly, Lattin et al (2015) supposed that the disruption of droplets may break down the membrane of endosome to aid the escape from the endosome endocytosis pathway of macromolecules such as genes.…”
Section: Dropletsmentioning
confidence: 99%